2007
DOI: 10.1080/08860220701260651
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Acute Renal Failure in a Developing Country: A Prospective Study

Abstract: Acute renal failure (ARF) occurs in wide range of conditions, making the evaluation of its prognosis a difficult task. Data regarding prognostic factors in ARF in a general population in developing countries are scarce. The objective of the study was to describe predictors of mortality in ARF that are relevant in the developing world. This prospective study was carried out over a one-year period; all hospitalized adults with ARF were included in the study. Predictors of mortality studied included causes of ARF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 19 publications
4
51
2
Order By: Relevance
“…Studies from developing countries have shown that AKI incidence varies (14,(19)(20)(21)(22)(23) and that AKI is often community acquired and preventable (i.e., due to gastroenteritis and infections) (23)(24)(25)(26)(27). However, a formal comparison between developed and emerging countries is lacking (14,28).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from developing countries have shown that AKI incidence varies (14,(19)(20)(21)(22)(23) and that AKI is often community acquired and preventable (i.e., due to gastroenteritis and infections) (23)(24)(25)(26)(27). However, a formal comparison between developed and emerging countries is lacking (14,28).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that in the USA 17 million admissions per year are complicated by AKI. 34 In developing countries AKI is a disease of the young [35][36][37] and children; 38,39 in developed countries it is a disease of the elderly. 40,41 With overall decreases in birth rate and mortality, life expectancy is increasing and is now longer than 80 years in most developed countries.…”
Section: Incidencementioning
confidence: 99%
“…The annual population growth rate is 2.4% and children under 15 years old constitute approximately 45% of the total population (1). It is well recognized that acute kidney injury (AKI) in developed countries affects the elderly more, while in developing countries AKI is a disease of the young and children in whom pre-renal causes are predominant (2,3).…”
mentioning
confidence: 99%